Fascinating bifunctional electrocatalytic activity via a mesoporous structured FeMnO3@ZrO2 matrix as an efficient cathode for Li-O2 batteries - Palani, Raja; Wu, Yi–Shiuan; Wu, She–Huang; Chien, Wenchen; Lue, Shingjiang Jessie; Jose, Rajan; Yang, Chunchen (American Chemical Society, 2023)
Nonaqueous Li-O2 batteries have remarkable potential for use in future-generation sustainable green energy storage systems. Perovskites of the type ABO3 provide bifunctional electrocatalytic activity superior to that of dual mixed-metal oxides due to the presence of crystallographic defects and oxygen vacancies, arising from the multivalency of the A and B cations. In this study, we used a facile hydrothermal method with an ammonia solution to modify coralline-like ZrO2 with Fe0.5Mn0.5O3 (FeMnO3) and graphene nanosheets (GNSs). The porous structure of the resulting ZrO2@FeMnO3/GNS system featured a high surface area and large volume, thereby exposing a great number of active sites. X-ray photoelectron spectroscopy revealed that the surface of the as-synthesized FeMnO3@ZrO2/GNS cathode material was rich with oxygen vacancies (i.e., a huge quantity of defects). This coralline-like bifunctional electrocatalyst possessed effective redox capability between Li2O2 and O2 as a result of its excellent catalytic activity in the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). We examined the charge/discharge behavior of corresponding electrodes (EL-cell type for Li-O2 battery) in the voltage range of 2.0-4.5 V (vs Li/Li+). The synergistic effects of the high catalytic ability and coralline-like microstructure of our ZrO2@FeMnO3/GNS catalyst for Li-O2 batteries resulted in its superior rate capability and excellent long-term cyclability, sustaining 100 cycles at 100 mA g-1 with a limited capacity of 1000 mAh g-1. The cell overpotential was ∼0.14 V when adding LiI as a redox mediator, resulting in a more practical Li-O2 battery with the ZrO2@FeMnO3/GNS catalyst. Therefore, ZrO2@FeMnO3/GNS catalysts having distinctive coralline-like structures can display outstanding bifunctional catalytic activity and electrical conductivity, suggesting great potential for enhanced Li-O2 battery applications.